PENYULUHAN PERTANIAN DI MERAUKE: KASUS DISTRIK SOTA SEBAGAI TAMAN NASIONAL DAN WILAYAH PERBATASAN - Demas Wamaer (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2007)
Sota it's one new districts of Merauke regency on 2005. The district is located in Taman Nasional Wasur and RI-PING (Republic of Indonesia-Papua New Guinea) boudary. The aim of the research is to assess agricultural extention of local peasant and to provide the solution by involving 6-8 peasant